The Triggering Process of an X-class Solar Flare on a Small Quadrupolar Active Region - Song, Qiao; Wang, Jing-Song; Zhang, Xiaoxin; Chen, Hechao; Yang, Shuhong; Hou, Zhenyong; Hou, Yijun; Ye, Qian; Zhang, Peng; Hu, Xiuqing; Dun, Jinping; Zong, Weiguo; et al. (The Astrophysical journal, 2023)
The occurrence of X-class solar flares and their potential impact on space weather often receive greater attention than other flares. But predicting when and where an X-class flare will occur is still a challenge. With the multiwavelength observation from the Solar Dynamics Observatory and FengYun-3E satellite, we investigate the triggering of a GOES X1.0 flare occurring in the NOAA active region (AR) 12887. Our results show that this unique X-class flare is bred in a relatively small but complex quadrupolar AR. Before the X-class flare, two filaments (F1 and F2) exist below a null-point topology of the quadrupolar AR. Magnetic field extrapolation and observation reveal that F1 and F2 correspond to two magnetic flux ropes with the same chirality and that their adjacent feet are respectively rooted at nonconjugated opposite polarities. Interestingly, these two polarities collide rapidly, accompanied by photospheric magnetic flux emergence, cancellation, and shear motion in the AR center. Above this site, F1 and F2 subsequently intersect with each other and merge into a longer filament (F3) via a tether-cutting-like reconnection process. As a result, F3 rises and erupts upward, eventually leading to a coronal mass ejection and the X-class flare. This observation suggests that the rapid collision of nonconjugated opposite polarities provides a key condition for the triggering of this X-class flare and also provides a featured case for a flare trigger mechanism and space weather forecasting.